Free education policy and hidden cost inequality: A literature review on indirect economic burdens on students’ families - Fadil, Khaidir; Arif, Mahmud; Alfaien, Noor Isna; Amran, Amran; Abroto, Abroto; Rahma, Ayunda (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3767, 2025)
The free education policy has become a global strategy to improve access to education, but in practice, it still leaves challenges in the form of hidden costs that continue to burden students' families, especially from low-income groups. This research aims to identify the types of indirect costs in free education and analyze their impact on the economic burden of families and access and quality of education. This study uses a library research approach with a qualitative-descriptive design and documentation techniques as data collection methods. Data sources are obtained from scholarly journal articles, books, policy reports, and relevant dissertations, which are analyzed using a thematic approach and content analysis. The results of the study show that costs such as uniforms, transportation, stationery, activity fees, and digital needs become significant burdens for poor families. This has an impact on disparities in participation, achievement, and learning experiences of students. This research concludes that free education is not yet fully economically inclusive and needs to be redesigned to include support for hidden costs. This study makes an important contribution to advocating for education policies based on distributive justice and opens up opportunities for further research with a field approach.